ANALISIS PENGARUH LEVERAGE, EFEKTIVITAS ASET DAN SALES TERHADAP PROFITABILITAS SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan di Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2007-2011) - Yuliana Dewi Putri Sari, Novia Maharani; Chabachib, Mochammad (Faculty of Economics and Business Diponegoro University, 2013)
Value of the firm became very important to the firm because investors always consider it before make investment decision. According to investor’s perception, value of the firm affected by firm financial performance because a good financial performance will give a great return to the investor and increase value of the firm. The previous research showed that there is a gap research, such as research by Nasehah (2012) and Hardiyanti (2012) have different result for observing the effect of Debt to Equity Ratio (DER) to Price to Book Value (PBV). Based on the data, it is known that there is a gap phenomenon. Therefore, further research is still needed. This study aims to analyze the effects of Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and sales towards Return on Asset (ROA) and the impact to Price to Book Value (PBV).This study uses firms in consumer goods industry listed in Indonesian Stock Exchange (IDX) from 2007 until 2011 as the population which consist of 38 firms. There are 31 firms selected as samples using purposive sampling method. This study uses secondary data obtained from published financial report in Indonesian Stock Exchange (IDX). Data analysis tool used was Path Analysis with the help of Structural Equation Modeling (SEM) with 19.0 AMOS program.The result of this research showed the following resulst; Debt to Equity Ratio (DER) has negative and significant effect on Return on Asset (ROA), Total Asset Turnover (TATO) has positive and significant effect on Return on Asset (ROA), Sales has positive and significant effect on Return on Asset (ROA), Debt to Equity Ratio (DER) has positive and significant effect on Price to Book Value (PBV), Sales has positive and significant effect on Price to Book Value (PBV), and Return on Asset (ROA) has positive and significant effect on Price to Book Value (PBV). The result of Path Analysis showed that Sales indirectly influence Price to Book Value (PBV) through Return on Asset (ROA).